Management of Regional Revenue and Expenditure Budgets at the Regional Financial Management Agency - Pentoria, Rina; Vaguita, Mercya; Meilina, Susiyanti (Adabi : Journal of Public Administration and Business, 2023)
This research aims to find out and understand the management of the regional revenue and expenditure budget at the South Solok Regency Regional Financial Management Agency, as well as the obstacles and efforts made. The type of research carried out was descriptive-qualitative. Researchers select informants according to certain predetermined criteria. Data collection techniques in this research used observation, interviews, and documentation studies. The data analysis technique in this research was carried out using four data analysis steps, namely data collection, data reduction, data presentation, and drawing conclusions. Based on the research results, it was found that managing regional income and expenditure budgets requires four stages, namely the planning, implementation, monitoring, and evaluation stages. In the monitoring stage, there are two important roles that must be played, namely community participation and NGOs. With the active and involved participation of the community and NGOs in monitoring the implementation of regional revenue and expenditure budgets, there has been a positive increase in the accountability of regional fund management. Technical obstacles to realizing accountability in managing regional revenue and expenditure budgets in South Solok Regency. Efforts to overcome obstacles in managing regional income and expenditure budgets in the BPKD of South Solok Regency include increasing supervision through internal and external audits, active community participation, and increasing the competence of village officials and organizational commitment. By involving all relevant parties and implementing mechanisms that allow for regular monitoring and evaluation, it is hoped that better accountability can be created in managing regional income and expenditure budgets.